IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Ihda Alam Niswatun Aminah; Mohammad Ahyan Yusuf Sya’bani (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2023)
The independent learning curriculum is a new policy initiative from the Ministry of Education and Culture of the Republic of Indonesia (Kemendikbud RI) announced by Nadiem Anwar Makarim. Textually, Islamic religious education is education based on Islamic teachings, namely those originating from the Qur'an and as-Sunnah. Islamic religious education guides students physically and spiritually based on Islamic religious norms towards the formation of a primary personality according to Islamic standards. The aim of implementing the independent curriculum as at SD Muhammadiyah 1 GKB Gresik is to overcome problems from previous education, the existence of this program will lead to the development of students' potential and competencies. The program functions to develop potential, one of which is a learning process that is designed in a relevant and interactive manner. The method used in this research is qualitative research. The purpose of this study was to explore the implementation of the independent curriculum in learning Islamic religious education at SD Muhammadiyah 1 GKB Gresik. Data collection is done by observation, interviews, and documentation. The data analysis technique used is an interactive analysis technique which includes data collection, data reduction, data presentation, then drawing a conclusion. The results of this research are the implementation of the independent learning curriculum in Islamic religious education learning in accordance with the policies of the Indonesian Ministry of Education and Culture, so that students are more enthusiastic about participating in the learning process with better learning creativity